KUALITAS PELAYANAN E-GOVERNANCE KIOS SIAPKERJA DI BALAI BESAR PELATIHAN VOKASI DAN PRODUKTIVITAS SERANG - Martalia, Wulan; Hartoko, Gatot; Saepudin, Eli Apud (Gapenas Publisher, 2025)
Advances in information technology have driven digital transformation, particularly in public services, including the employment sector. The Indonesian Ministry of Manpower has designed SIAPkerja as a digital ecosystem that integrates employment services at the Technical Implementation Unit of the Serang Productivity Vocational Training Center. However, the implementation of digital services still faces obstacles, particularly in terms of public digital literacy. The SIAPkerja kiosk serves as a service facility to facilitate digital access. This study aims to evaluate the quality of the SIAPkerja kiosk service and identify the factors that support and hinder digital services through the SIAPkerja application.This study uses a qualitative descriptive approach based on the Service Quality model developed by Parasuraman, Zeithaml, and Berry 1990. This model includes five dimensions of service quality assessment, namely Tangibles (physical evidence), Reliability (dependability), Responsiveness (responsiveness), Assurance (assurance), and Empathy (empathy). Data collection techniques involved in-depth interviews with management, service officers, prospective participants, and training alumni. The findings show that, in general, the quality of SIAPkerja Kios service is good in terms of physical facilities and assistance from officers. Supporting factors include responsiveness, completeness of facilities, and dissemination of information on social media. Meanwhile, the inhibiting factors include the low level of digital literacy among users and the lack of accessible self-guided media. Therefore, continuous digital education and strengthening the role of Kios as a digital literacy center are needed so that the community can access E-Governance services independently and sustainably.